76 Are complications during pregnancy in women with mechanical heart valves influenced by their choice of anticoagulation?. (5th June 2017) - Parry, Helen; English, Kate; Oliver, James; Cullington, Damien; Ciantar, Etienne; Simpson, Nigel; Winfield, Sarah; Norfolk, Derek
Abstract : Introduction: Anticoagulation during pregnancy in women with mechanical valves is complex. Strategies include warfarin or low-molecular weight heparin (LMWH) throughout or LWMH during first trimester then warfarin until delivery. Warfarin poses risks of teratogenicity and fetal haemorrhage. However, LMWH poses increased thrombotic risk and frequent difficulties maintaining therapeutic peak and trough anti-Xa levels. We aimed to assess the complication rate in pregnant women with mechanical valves and whether anti-Xa levels were maintained within the recommended range with LMWH Methods: All pregnant women with mechanical valves under the ACHD team at Leeds General Infirmary were identified 2001- 2016. Medical records and blood results were analysed, identifying thrombotic and haemorrhagic complications, pregnancies leading to delivery of a healthy child and efficacy of anti-factor Xa monitoring. Results: The 12 patients identified had 25 pregnancies; 12 ultimately delivered a healthy child, 2 of which had no complications. Thrombotic events complicated 6 pregnancies, haemorrhage complicated 5 pregnancies and 1 pregnancy was complicated by both (including all pregnancies/miscarriages). Three pregnancies underwent planned termination, 7 miscarried pre-8 weeks gestation with 3 intra-uterine deaths. Ten patients used LMWH in the first trimester only and 5 used LMWH throughout pregnancy. The graph shows peak anti-factor Xa levels measured closest to complication development or average peak level if there were no complications (where measurements were available). The peak target was 1.0–1.2. Conclusions: Pregnancy in women with ACHD and mechanical valves carried significant risk of haemorrhage and thrombosis, regardless of anti-coagulation strategy. Anti-Xa levels were generally not maintained within target range.